Design and development of a multi-user virtual learning environment using second life and effectiveness in improving residents a chievement and knowledge retention - Pany, Richard Hari Chandra (2012)
The recent development of digital tools has spurred educators to think differently about how they teach and how they can use computers in their classrooms. The concept of Multi-User Virtual Environments (MUVEs) has opened new avenues in the educational spectrum. The use of virtual worlds, in particular Second Life, in higher education has been the focus of study, in evaluating the value of Second Life in a hybrid implementation of forensic science course. This thesis is based on such an experiment carried out where students in an Introductory Forensic Science module use Second Life as their platform. Both quantitative and qualitative investigation processes provide the researcher with different ways of operationalizing and measuring theoretical constructs and practical concepts. Quantitative methods ensured high levels of reliability of gathered data on the students' achievement and knowledge retention. Qualitative research allowed for obtaining more in-depth information about how the students engagement level using Second Life as a platform. The findings are based on data collected from student surveys, student interviews, test scores and observations collected over the course of the experiment. The majority of the students acknowledged the value of Multi-User Virtual Environment in Second Life and demonstrated improved engagement and learning in many instances through detailed experiences, higher achievement scores and retention of the subject matter. The conclusions of the study suggest that the combination of MUVEs' features and strengths will eventually influence the educators to accept the MUVE as an educational tool, although several areas of concern are identified. Future growth in the educational uses of MUVEs is examined, the implications and limitations of the study are discussed, and ideas for future research are elaborated on.